Students' Reading Anxiety: A Rasch Model Analysis - Nur halimah; Gatot Subroto; Nana Raihana Askurny (Universitas Maritim Raja Ali Haji (UMRAH), 2021)
The aim of this study is to determine the instrument and the students’ responses of reading anxiety. The approach of this research is qualitative descriptive. The gathered data were analyzed qualitatively by using Rasch Model. A questionnaire was used as an instrument to get the data. 14 female students of SMP Islam De Green Camp were involved in this research. The FLRAS by Horwitz et al was used to create a questionnaire that contained 20 items. The study showed that the quality of the instrument and the students’ responses were not good enough to be used due to their small amount. Therefore, teachers must choose and creates a good instrument to know their students’ responses about reading anxiety. Then, students are recommended to read more English texts to minimize their reading anxiety.